Identification of the Occipito-Pontine Tract Using Diffusion-Tensor Fiber Tracking in Adult-Onset Adrenoleukodystrophy with Topographic Disorientation - Yuji Uchida; En Kimura; Teruyuki Hirano; Shinsuke Nishi; Yasushi Maeda; Satoshi Yamashita; Keiko Ueno-Shuto; Naofumi Tokutomi; Mika Kitajima; Toshinori Hirai; Makoto Uchino (Case Reports in Neurology, 2011)
X-linked adrenoleukodystrophy is a severe and progressive neurodegenerative disease caused by the peroxisomal transporter ATP-binding cassette, subfamily D, member 1 gene mutations. The defect of this gene product results in accumulation of very-long-chain fatty acids in organs and serum, central demyelination, and peripheral axonopathy. Although there are different magnetic resonance (MR) findings which reflect various phenotypes in adrenoleukodystrophy, some cases present with specific symmetrical occipital white-matter lesions. We describe a patient with adult-onset X-linked adrenoleukodystrophy with topographic disorientation, whose brain MR images revealed T2-signal hyperintensity along the occipito-pontine tract and lateral lemnisci, but not in the cortico-spinal tract in the brainstem. The occipito-pontine tract and lateral lemnisci were clearly detected using diffusion-tensor fiber tracking, suggesting that the topographic disorientation of this patient might be related to the occipito-pontine tract. MR tractography can effectively identify the occipito-pontine tract and may help to localize the fibers associated with clinical symptoms.